Institution of the plenipotentiary ombudsman for human rights in Tajikistan in the normative and practical dimension - Szukalski, Jerzy (Polityka i Społeczeństwo, 2023)
The office of the Plenipotentiary Ombudsman for Human Rights was established in Tajikistan on the basis of a relevant bill adopted on March 20, 2008. Statutory regulations normalize every important issue concerning the organization and modes of operation of the ombudsman. Fundamentally they generally meet the standards of analogous acts in force in democratic states. In the normative dimension, one can only object to the method of selecting the Ombudsman, dependent on the President of Tajikistan, which, in turn, questions his independence from the presidential center of power. On the other hand, in the practical dimension, within the reality of the authoritarian system functioning in Tajikistan, the Ombudsman's institution is a façade and is not able to fulfill the functions for which it was appointed. This is evidenced by the Ombudsman's reports, clearly lacking cases relating to first-generation human rights.